Effects of microRNA‐217 on proliferation, apoptosis, and autophagy of hepatocytes in rat models of CCL4‐induced liver injury by targeting NAT2. Issue 4 (11th November 2018) - Yang, Cheng‐Liang; Zheng, Xiao‐Li; Ye, Ke; Sun, Ya‐Nan; Lu, Yu‐Fei; Ge, Hong; Liu, Hui
Abstract: Liver injury is an important cause of serious liver disease. This study aims to explore the effects of miR‐217 targeting NAT2 on hepatocyte proliferation, apoptosis, and autophagy following carbon tetrachloride (CCL4)‐induced liver injury. Rat models of CCL4‐induced liver injury were established. Healthy Wistar rats were randomized into the normal, blank, negative control (NC), microRNA‐217 (miR‐217) mimic, miR‐217 inhibitor, small interfering RNA (siRNA)‐ N ‐acetyltransferase 2 (NAT2), and miR‐217 inhibitor + siRNA‐NAT2 groups. NAT2 activity was evaluated with reversed‐phase high‐performance liquid chromatographic method. Immunohistochemistry was used to detect NAT2 protein positive rate. Reverse transcription quantitative polymerase chain reaction and western blot analysis were used to examine expressions of miR‐217, NAT2, Bcl‐2, Bax, p35, LC3‐II, Becline‐1, and the ratio of caspase‐3/cleaved caspase‐3. Autophagy, proliferation, and cell cycle distribution were determined by electron microscope, CCK‐8, and flow cytometry. NAT2 protein positive rate and miR‐217, NAT2, Bcl‐2, and p35 expressions were higher and Bax, LC3‐II, and Becline‐1 expressions and the ratio of caspase‐3/cleaved caspase‐3 lower in the normal group than the other six groups. Compared with the blank and NC groups, in the miR‐217 mimic and siRNA‐NAT2 groups, Bax, LC3‐II, and Becline‐1 expressions and the ratio of caspase‐3/cleaved caspase‐3, and hepatocyte apoptosis and autophagy increased, while NAT2, Bcl‐2, and p35 expressions and hepatocyte proliferation decreased; opposite results were observed in the miR‐217 inhibitor group. Collectively, miR‐217 targeting NAT2 inhibits proliferation and promotes apoptosis and autophagy of hepatocytes in CCL4‐induced liver injury. Abstract : miR‐217 targeting NAT2 inhibits proliferation and promotes apoptosis and autophagy of hepatocytes in CCL4‐induced liver injury.